(untitled) (Journal of Science-Innovative Research in Uzbekistan, 2023)
This article delves into the practical implementation of the finite element method (FEM) for the comprehensive examination of fluid flows within channels. It begins by introducing FEM as a numerical solution to the intricate partial differential equations governing fluid dynamics. Emphasizing clarity in methodology, the discussion progresses to cover key aspects such as mesh generation and element interpolation, revealing how the domain is systematically divided into finite elements, and nodal values are strategically utilized for fluid behavior approximation. The assembly of system equations, incorporating boundary conditions, and the subsequent solution process are explored, with a focus on obtaining accurate results. The article also underscores the advantages of FEM, including its adaptability to complex geometries and its utility in diverse flow scenarios. Crucial considerations, such as validation and iterative refinement, are highlighted for ensuring the reliability of the simulations, offering readers a comprehensive guide to employing FEM for in-depth studies of fluid flows in channels.